Impact of interactions between risk alleles on clinical endpoints in hypertension. Issue 1 (19th May 2016) - Kohli, Samantha; Kumar, Rahul; Gupta, Mohit; Tyagi, Sanjay; Pasha, M A Qadar
Abstract : Objective: Impairment of the renin-angiotensinogen-aldosterone system (RAAS), one of the characteristics of essential hypertension (EH), imbalances vascular homeostasis. Despite inconsistent reports on individual single nucleotide polymorphisms (SNPs) as a major predictor of EH, interactions among RAAS genetic variants are rarely investigated. Methods: Using SNP markers, we studied potential interactions between angiotensin 1 converting enzyme ( ACE ), angiotensinogen ( AGT ), angiotensin II-type 1 receptor ( AGTR1 ), and α adducin ( ADD1 ) variants and their correlation with clinical endpoints in 545 individuals with hypertension and 400 age- and ethnicity-matched unrelated controls. Generalised multifactor dimensionality reduction (GMDR) analysis identified the models for genotype interaction. Results: Although the results on single genes were significant, gene-gene interactions were more reliable and promising as markers in predisposing hypertension. The best models to represent association of multi-locus interactions with augmented hypertension susceptibility were: (a) within gene 4-locus model comprised of AGT SNPs −217G/A, −20A/C, −6G/A and 235M/T (p=0.022, OR 6.1); and (b) between genes 5-locus model comprised of AGT −217G/A, −20A/C, −6G/A, 235M/T and ACE I/D (p=0.05, OR 4.6). Stratification of 4- and 5-locus GMDR models on the basis of risk alleles from ≤1 to ≥7 increased the ORs from 2.8 to 36.1 and from 0.9 to 16.1, respectively. Moreover, compared to ≤1 risk alleles the ≥7 interacting risk alleles in both 4- and 5-locus models showed an increment of 14.2% and 11.1% in systolic blood pressure, 7.7% and 1.1% in diastolic blood pressure, and 10.5% and 5.1% in mean arterial pressure, respectively, in patients. Conclusions: Interactions among the genetic loci of RAAS components may be used as a predictor for susceptibility to hypertension.